The Effect of Organizational Culture on Employee Performance with Emotional Intelligence as an Intervening Variable in the Public Works Department And Spatial Planning for Binjai City - Zulham Juniandri Lubis; Muhammad Isa Indrawan (International Journal of Economics, Management and Accounting (IJEMA), 2023)
In facing globalization, human resource management plays an important role in company activities. This study aims to analyze the influence of organizational culture on employee performance with emotional intelligence as an intervening variable. This research was conducted at the Public Works and Spatial Planning Office of the City of Binjai. The population of this research is 79 employees. The sample used is a saturated sample. The research model uses path analysis as a measuring tool using smart PLS version 3.3.3. The results of this study are Organizational Culture has a positive and significant effect on Emotional Intelligence. Organizational Culture has a positive and significant effect on Employee Performance. Emotional intelligence has no significant positive effect on employee performance.